Effects of Virtual Laboratory and Gender on the Learning Outcomes of Undergraduate Physics Students in Ohm’s Law Verification - Shedrack, Tamunoiyowuna; Godpower-Echie, Glory; Ikiroma, Blessing (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
This study examined virtual laboratory effect and gender on the verification of ohm's law and undergraduate physics students' performance and retention in Ignatius Ajuru University of Education, Port Harcourt. Quasi experimental of the type, pretest-posttest, post-posttest control group design was adopted for this study. The population of the study comprised all year 2 undergraduate physics students of Ignatius Ajuru University of Education, numbering one hundred and eight (108). "Simple Random Sampling Technique was employed to get a sample size of seventy-two (72). Four research questions and four hypotheses were formulated to guide this study. An experimental group and a control group were used for the study. The experimental group was taught practical physics using a virtual laboratory (Circuit lab software) while the control group was taught using the hands-on laboratory. The instrument used for this study is a test titled "Physics Practical Test on the Verification of Ohm's Law (PPTVOL)". A reliability index of 0.72 was obtained for (PPTVOL) using the test-retest method. Data were analyzed using mean and standard deviation to answer the research questions while a t-test was used to test the hypotheses at 0.05 level of significance." The findings of the study revealed that the use of a virtual laboratory in practical physics does not have a significant effect on gender as regards performance and retention. It was also found that the use of hands-on laboratory does not have a significant effect on gender as regards performance and retention. This study recommends that physics lecturers should use virtual laboratories for teaching practicals.